VISUAL AND MICROSCOPIC EVALUATION OF THE SURFACE ALTERATIONS IN THE PROTAPER FILES AFTER SINGLE CLINICAL USE - Aziz, Surhan; Ghafoor, Robia; Gul, Meisha; Khan, Farhan Raza (Journal of Ayub Medical College Abbottabad, 2018)
Background: Different studies have been conducted in which defects of Ni-Ti files were reported after multiple usages but limited data is available regarding the defects in the rotary Ni-Ti files subjected to single clinical use. The objective of this study was to determine the frequency of surface defects caused by fatigue in the rotary ProTaper files after single clinical use assessed with visual and microscopic examination methods. Methods: A cross-sectional study was conducted in the dental clinics of The Aga Khan University Hospital, Karachi, Pakistan. A total of 189 ProTaper Ni-Ti files (after single clinical use in multi-rooted molars) were analysed visually and then under stereomicroscope at 10Î§ magnification for surface defects (straightening, denting, bending, twisting, pitting and change in length). Chi Square test was used to determine association between type of file and type of defect. Spearman's correlation test was used for determination of correlation between visual and microscopic examinations at 0.05 level of significance. Results: 19% of files showed straightening on visual assessment as compared to 66.1% under microscopic examination. There was a statistically significant association between the file type and the straightening of file (p value ‰¤0.001). A weak correlation existed between visual and microscopic examination for all the defects, except for the change in length. Conclusions: The defects of ProTapers files are best detected by the microscopic examination. Straightening is the most common defect observed visually and microscopically. The first shaping and first finishing files underwent significantly more surface defects than the rest of the rotary files in the series. Keywords: Defects; Evaluation; Instrumentation; Root canal; Root canal therapy